Islamic Revivalism: Dynamics of Islamic Parties in Legalizing Islamic Law Policies in Indonesia and Malaysia - Dewi, Siti Malaiha; Syamsudin, Muhammad Hasan; Alatas, Alwi; Muhsin, Ilyya (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This study aims to fill the gap and explore how Islamic parties have attempted to legalize Islamic law in both countries over the past three decades. Most scholarly works on Islamic revivalism in Indonesia and Malaysia focus on it as a sociocultural phenomenon. However, there is a lack of scholarship investigating Islamic revivalism through a political approach. This article employs qualitative research methodology, drawing on academic books, journal articles, reports, and online news to examine the efforts of Islamic parties to legalize Islamic law in Indonesia and Malaysia. The findings suggest that the accessibility of political channels significantly influences these efforts. During the Mahathir era in Malaysia, the availability of political channels facilitated the goal of legalizing Islamic law. Conversely, the agenda for legalizing Islamic law was hindered in Indonesia during the Soeharto era due to limited political channels. Additionally, the moderation of Islamic parties affects the agenda for legalizing Islamic law in both countries. In post-Soeharto Indonesia, the incorporation of moderation by Islamic parties has led to a decrease in prioritizing the agenda of legalizing Islamic law. On the other hand, in Malaysia during and after the Mahathir era, the persistence of the obsession with legalizing Islamic law was due to Islamic parties distancing themselves from moderate positions.